Guest

(sec A - cosec A)(1+ tan A + cot A) = tan A sec A- cot A cosec A

(sec A - cosec A)(1+ tan A + cot A) = tan A sec A- cot A cosec A

Grade:10

4 Answers

Saurabh Koranglekar
askIITians Faculty 10335 Points
2 years ago
Dear student

Please ask complete question

Regards
Vikas TU
14149 Points
2 years ago
Dear student 
1/CosA - 1/SinA (1+sinA/CosA + CosA/SinA)
= (SinA-cosA)/SinAcosA)((SinACosA + Sin^2A + Cos^2A)/(SinACosA)
=(Sin^3A - Cos^3A) /SinA CosA
= TanA SecA - CotACosecA
 
Arun
25758 Points
2 years ago
 
Dear student
 
LHS
(1/ cosA  - 1/sinA ) (1 + sinA/cosA + cosA /sinA)
= ((SinA-cosA)/sinA cosA)((sinA cosA + sin²A + cos²A)/sinA cos A)
= (Sin³A - cos³A)/ sinA cosA
= TanA secA - cotA cosecA
 
RHS
 
Hence proved.
 
Yashraj
915 Points
2 years ago
please ask what to do in this question 
with my best regards
type the full question 
or attach the image

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free